The Imaging Appearance of 'EWSR1::PATZ1' Gene Fusion Central Nervous System Tumors - Cedric Vanmarcke; Lukas Marcelis; Isabelle Vanden Bempt; Raf Sciot; Johannes Devos (Journal of the Belgian Society of Radiology)
Ewing Sarcoma Breakpoint Region 1 and POZ/BTB And AT Hook Containing Zinc Finger 1 (EWSR1::PATZ1) gene fusion central nervous system (CNS) tumors are increasingly recognized as a potential distinct entity, with only limited reported cases. The imaging characteristics of these tumors have not been well established. In this study, we provide a detailed radiological description of a case in a 24‑year‑old man and conduct a literature review to identify common imaging features. A total of seven cases, including our own, were evaluated. Histopathological diagnoses included two ependymomas, an infantile glioblastoma, an astroblastoma, a ganglioglioma, and two gliomas not otherwise specified. Common imaging patterns included avid contrast enhancement, intratumoral cysts, intraventricular location or extension leading to hydrocephalus, and sharp delineation. Additional frequently observed features included calcifications and hemorrhagic foci. In conclusion, although the histopathological appearance of EWSR1::PATZ1 gene fusion CNS tumors is diverse, there are consistent imaging features. Recognition of these features can be valuable in the diagnostic process, as radiologists can be the first to suggest the diagnosis.